2015
DOI: 10.1073/pnas.1508330112
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiological oscillators control lymph flow

Abstract: The ability of cells to sense and respond to physical forces has been recognized for decades, but researchers are only beginning to appreciate the fundamental importance of mechanical signals in biology. At the larger scale, there has been increased interest in the collective organization of cells and their ability to produce complex, "emergent" behaviors. Often, these complex behaviors result in tissue-level control mechanisms that manifest as biological oscillators, such as observed in fireflies, heartbeats,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 84 publications
(95 citation statements)
references
References 77 publications
2
93
0
Order By: Relevance
“…NIRF imaging showed that the lowest contraction frequency was measured after an injection of 20 μl of contrast agent ( Figure 2D). This is similar to what others have reported in ex vivo measurements of lymphatic vessels when a favorable pressure gradient was imposed, likely causing a shear-dependent response (18,20,(24)(25)(26). (Figure 2, A-D and Supplemental Videos 1-3; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.96591DS1).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…NIRF imaging showed that the lowest contraction frequency was measured after an injection of 20 μl of contrast agent ( Figure 2D). This is similar to what others have reported in ex vivo measurements of lymphatic vessels when a favorable pressure gradient was imposed, likely causing a shear-dependent response (18,20,(24)(25)(26). (Figure 2, A-D and Supplemental Videos 1-3; supplemental material available online with this article; https://doi.org/10.1172/jci.insight.96591DS1).…”
Section: Resultssupporting
confidence: 88%
“…Lymphatic contraction reduction in the presence of increased flow suggests there is flow-mediated dilation and contraction inhibition due to the presence of a favorable upstream pressure gradient, which has been reported via ex vivo analysis of lymphatic vessels subjected to step-wise increasing pressures (18,20,(24)(25)(26). Similar results of increased lymph flow have been reported with intravital imaging of rats experiencing edemagenic stress (30).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The fact that NO is produced through endothelial nitric oxide synthase (eNOS) in response to fluid shear forces allows it to establish another mechanobiological feedback system that, together with stretch-activated calcium channels, can help control the phasic contractions (91). Endothelium-derived relaxing factors such as NO provide a counterbalance to calcium-induced contractions, maintaining vessel dilation in circumstances when low resistance is needed to allow pressure-driven flow (78).…”
Section: Lymphatic Transport and Pumpingmentioning
confidence: 99%
“…Computational modeling shows that the mechanosensitive calcium and NO dynamics can cooperate to control lymphatic transport via mechanobiological feedback loops (91): During a lymphatic contraction cycle, increased flow causes local eNOS activation, and the subsequent production of NO attenuates and/or reverses the Ca 2+ -dependent contraction (Figure 3). As the vessel relaxes, NO degrades rapidly and its production drops due to the reduced fluid velocity in the now-larger-diameter vessel.…”
Section: Lymphatic Transport and Pumpingmentioning
confidence: 99%